Transformational Leadership in Developing Student Character through Extracurricular Activities: A Case Study in an Indonesian Elementary School - Jamaludin; Inaya Sari Melati (Universitas Negeri Semarang, 2025)
The purpose of this study is to construct a model of principal leadership in developing student character through extracurricular activities in resource-limited elementary schools. The method used was qualitative with an intrinsic case study design at SD Negeri Mendala 01, Brebes. Data were collected through in-depth interviews, participatory observation, and documentary studies, then analyzed interactively. The results show that: (1) The principal's transformational leadership demonstrated through exemplary behavior, inspirational vision, teacher empowerment, and clinical supervision is the main driver of the character ecosystem; (2) Extracurricular activities (Scouting, Volleyball, Arts, Theater, Painting) function as a